Apical-out intestinal organoids as an alternative model for evaluating deoxynivalenol toxicity and Lactobacillus detoxification in bovine - Min Gook Lee; Bo Ram Lee; Poongyeon Lee; Soyoung Choi; Jong-Hui Kim; Mi-Hwa Oh; Jae Gyu Yoo (Scientific Reports)
Abstract Small intestinal organoids are similar to actual small intestines in structure and function and can be used in various fields, such as nutrition, disease, and toxicity research. However, the basal-out type is difficult to homogenize because of the diversity of cell sizes and types, and the Matrigel-based culture conditions. Contrastingly, the apical-out form of small intestinal organoids is relatively uniform and easy to manipulate without Matrigel. Therefore, we sought to investigate the possibility of replacing animal testing with bovine apical-out small intestinal organoids (Apo-IOs) by confirming the toxicity of mycotoxins and effectiveness of L. plantarum as mycotoxin-reducing agents. The characteristics and functions of Apo-IOs were first confirmed. The gene and protein expression of stem cell, proliferation, mucous, and adherence markers were detected, and the absorption capacity of amino and fatty acids was also confirmed. FITC-4 kDa dextran, a marker of intestinal barrier function, did not penetrate the Apo-IOs, confirming the role of the organoids as a barrier. However, when co-treated with deoxynivalenol (DON), FITC-4 kDa dextran was detected deep within the organoids. Moreover, qPCR and immunofluorescence staining confirmed a decrease in the expression of key markers, such as LGR5, Ki67, Mucin2, Villin2, and E-cadherin. In addition, when Apo-IOs were treated with Lactobacillus plantarum ATCC14917 culture supernatant (LCS) and DON together, cell death was reduced compared to when treated with DON alone, and FITC-4 kDa dextran was confirmed to flow only to the peripheral part of the organoid. The qPCR and immunofluorescence staining results of LCS and DON co-treatment group showed that LGR5, Ki67, Mucin2, Villin2, and E-cadherin were expressed at significant higher levels than those in the DON treatment group alone. In this study, we found that the characteristics and functions of bovine Apo-IOs were similar to those of the intestinal structure in vivo. Additionally, the effects of mycotoxins and effectiveness of L. plantarum as mycotoxin-reducing agents were confirmed using bovine Apo-IOs. Therefore, bovine Apo-IOs could be applied in toxicity studies of mycotoxins and could also be used as in vitro models to replace animal testing and improve animal welfare.